Mineralogia e geoquímica de sedimentos de manguezais da costa amazônica: o exemplo do estuário do rio Marapanim (Pará) - BERRÊDO, José Francisco (2015)
The mangroves of the Para state represents an important segment of the Brazilian north coast on the ones which little it is known of the geological characteristics and it relationships with source areas. This research was accomplished in the Marapanim river estuary, in the Para coast, to demonstrate the contribution of continental sediments for the constititution of the mangrove's sediments. The mangrove's sediments and the Barreiras Formation sediments and soils (main continental sources) were collected. In the mangrove's sediments grain size, determination of the carbon (C%), pH and Eh measures and interstitial salinity was made. The mineralogical determination and the multi-elementary geochemistry was made in the sediments muddy and terrigenous adjacents sediments for comparisons. The mangrove's sediments are clayey silty (> 90%), with the carbon values among 0,75 to 3,5%. The main mineralogy is composed by quartz, goethita, hematite, kaolinite, illite, besides zircon, tourmaline, staurolite and cianite as accessories, what indicates contribution of the Barreiras Formation sediments and sediments muddy. It is common the occurrence in these mangroves the neoformated minerals as: smectite, K-felspars, pyrite, halite, gipsum and jarosite. The enrichment in SiO2, Al2O3, Fe2O3 and TiO2 in the mangroves and the low tenors in trace metals reflects the tropical climate and the mineralogical composition of the source area, enriched in quartz and caulinite, with low tenors in K2O, Na2O, MgO and CaO. The chemical composition associated to the organic matter, abundant diatoms besides Fe, S and the marine contributions of Cl-, Na+, K+, Ca++ and Mg++, identify the deposicional ambient and the autigenics minerals. The concentrations and the geochemical behaviour of the trace metals in the mangroves corroborates the outstanding contribution of the continental source area. Those sediments presents the prevalence of the Light Rare Earth Elements (LREE) on the Heavy Rare Earth Elements (HREE) with high reasons of Th/Co; La/Th; La/Sc; La/Co and Zr/Sc and Th/Sc and Ba/Co, elements present in the felsic igneous rocks that originated the continental sediments.